Pattern of Animal Bites and Delays in Initiating Rabies Postexposure Prophylaxis among Clients Receiving Care in Korle-Bu Teaching Hospital - Nuertey, B.D.; Addai, J.A. (Journal of Tropical Medicine, 2020)
Introduction. Each year, an estimated 25000 rabies death occurs in Africa. Post-exposure prophylaxis (PEP) remains the only proven approach in preventing rabies deaths. Most of rabies deaths occur among those who delayed, did not receive, or complete rabies PEP. )e aim of this study was to determine the pattern of animal bite, factors associated with delays in initiating, and nonadherence to rabies PEP regimen. Method. Data on clients reporting for rabies PEP in a tertiary hospital setting in Ghana were collected from 2013 to 2016. Demographics, place, and source of exposure were collected. Other information obtained included adherence to the PEP protocol and GPS coordinates of the town of animal bites. )e shortest distance between the GPS coordinates of town of animal bite and the site of administration of the rabies PEP was calculated. A total of 1030 individuals received rabies PEP over the period. Results. Overall, 52.9% (545) were males while 47.1% (485) were females. Majority of the cases were between the age group 1–10 years accounting for 29.2%. Dog bites accounted for 96.5% (n = 994). Cats, nonhuman primates, human bites, respectively, accounted for 1.8% (n = 18), 1.2% (n = 12), and 0.6% (n = 6) of all bites. Majority of bites occurred at home (66.2% (n = 646)). Also, 31.6% (n =308) and 2.3% (n =22) of bites occurred on the streets and neighbors/friends’ homes, respectively. Only, 18.7% initiated PEP within 24 hours of bite. Rabies PEP regimen completion rate was 95.2% (n = 976). )e median distance travelled to access rabies PEP was 7.87 km (IQR, 3.58–16.27) km. Overall, 34.7% (n = 344) had the animal bite within 4.99 km radius of the treatment room of KBTH. Clients who delayed in initiating rabies PEP were 2.6 (95% CI, 1.3–5.1) times more likely to be males and 2.0 (1.1–3.9) times more likely to receive bites in a location more than 5 km radius from the KBTH treatment room. Gender, age, and distance of bite from the treatment room were not associated with the likelihood of not completing rabies PEP schedule. Discussion. Bites from suspected rabies infected animals remain a problem in southern Ghana. )ere are significant delays in initiating PEP for rabies prevention. Most animal bite victims are children ten years and below. Male gender and bites more than 5 km radius from the site of rabies PEP administration were most significant factors associated with delays in initiating rabies PEP. )ere is the need for adopting strategies to encourage prompt initiation and adherence to PEP.
Research Article
Keywords: Post-exposure prophylaxis (PEP); rabies prevention; KBTH treatment room; PEP administration